Prediksi Tingkat Kriminalitas Menggunakan Metode Single Moving Average - Mustopa Husein Lubis; S Sumijan (Jurnal Sistim Informasi dan Teknologi, 2021)
Crime is all kinds of actions and actions that are economically and psychologically harmful that violate the laws in force in the State of Indonesia as well as social and religious norms. Ordinary criminal acts affect the security of the community and threaten their inner and outer peace. The research location is the Asahan Police which is an agency that can provide security and protection for the community, especially those in Asahan Regency. The problem that occurs in this location is that there is no prediction system in Asahan Regency, due to the lack of knowledge factor in processing crime rate data. So it is difficult to know how much the increase or decrease in criminal cases carried out at the Asahan Police. The data used are cases of murder, sexual harassment, assault, violent theft, weight theft, motorcycle theft, fraud and counterfeiting money for the last 5 years from 2016 to 2020. This study aims to predict the crime rate in Asahan Regency in order to anticipating the upcoming spike in crime. The system that will be made uses forecasting or forecasting. With the Single Moving Average forecasting method. The Single Moving Average method is a forecast for the time in the future. The results of the calculation of predictions for criminal cases in 2021 obtained 3 cases of murder, 2 cases of sexual harassment in 2021, 252 cases of maltreatment in 2021, 27 cases of violent theft in 2021, 348 thefts with a weight in 2021. cases, motorcycle theft in 2021, totaling 90 cases, fraud in 2021, amounting to 85 cases, and counterfeiting money in 2021, totaling 1 case. This result has an accuracy rate of 99% from the reality of the crime that occurred, so this study is very appropriate to be used to predict the crime rate.